2023
DOI: 10.1029/2023gl104887
|View full text |Cite
|
Sign up to set email alerts
|

The Attachment Process of Negative Connecting Leader to the Lateral Surface of Downward Positive Leader in a Positive Cloud‐To‐Ground Lightning Flash

Qi Qi,
Bin Wu,
Weitao Lyu
et al.

Abstract: Using high‐speed video cameras operating with framing rates of 20 and 50 kiloframes per second, we captured an attachment process during a positive cloud‐to‐ground flash, which demonstrates the connection of the negative connecting leader (NCL) to the lateral surface of the downward positive leader (DPL) for the first time. When the NCL was initiated, the tip of the DPL had passed the initiation position of the NCL for about 50 m. A common streamer zone (CSZ) was observed when the three‐dimensional distance be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Qi et al. (2023) observed a branchless downward positive leader that gradually accelerated between heights of 1,500 and 580 m above ground level. The 2D speed increased from 1.2 × 10 5 m/s to 16.4 × 10 5 m/s with an average of 5.6 × 10 5 m/s, while the corresponding 3D speed increased from 3.7 × 10 5 m/s to 21.9 × 10 5 m/s with an average of about 10 6 m/s.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Qi et al. (2023) observed a branchless downward positive leader that gradually accelerated between heights of 1,500 and 580 m above ground level. The 2D speed increased from 1.2 × 10 5 m/s to 16.4 × 10 5 m/s with an average of 5.6 × 10 5 m/s, while the corresponding 3D speed increased from 3.7 × 10 5 m/s to 21.9 × 10 5 m/s with an average of about 10 6 m/s.…”
Section: Introductionmentioning
confidence: 99%
“…In a follow-up study, Saba et al ( 2010) examined 29 downward positive leaders (including nine presented by Saba et al (2008)) and found the mean 2D speed of 2.76 × 10 5 m/s, with the range being 2.4 × 10 4 to 1.18 × 10 6 m/s, They also reported that, for a subset of 28 leaders, 82% accelerated as they approached the ground, 7% decelerated, and 11% exhibited a non-monotonic speed variation. Qi et al (2023) observed a branchless downward positive leader that gradually accelerated between heights of 1,500 and 580 m above ground level. The 2D speed increased from 1.2 × 10 5 m/s to 16.4 × 10 5 m/s with an average of 5.6 × 10 5 m/s, while the corresponding 3D speed increased from 3.7 × 10 5 m/s to 21.9 × 10 5 m/s with an average of about 10 6 m/s.…”
mentioning
confidence: 98%